Prenatal and preimplantation diagnosis in the light of the Magisterum of the Catholic Curch - Golser, Karl (Medicina e Morale, 1999)
The study summarises the affirmation of the Evangelium Vitae Encyclical and the Congregation for the Doctrine of Faith document Donum Vitae about the possibility of prenatal diagnosis. The main point of these documents is the absolute defence of human life from conception on. Therefore, prenatal diagnosis is morally acceptable only if it does not damage the embryo or of the foetus and if it is therapy-oriented - and not suppressive. The issue related to preimplantation diagnosis are examined through French Bishops' document and a German Bishops' one, whereas the two pontifical documents mentioned above do not discuss it. Indeed, this problem must be seen in a different moral perspective, since it has so far involved defective embryos' screening and destruction. This is an eugenics practice and clearly goes against the defence of every human life principle.